Peran Penggunaan Bahasa Indonesia Sebagai Kontrol Sosial Untuk Menghindari Perundungan di SMA Negeri 6 Palopo - Yusni, Yusni; Nasir, Citra; Mattoliang, Ridwan Andi (Penerbit Widina, Widina Media Utama, 2025)
Bullying involves the abuse of power to harm individuals or groups through verbal, physical, or psychological means, causing victims to feel depressed, traumatized, and helpless. Adolescents who experience bullying are at higher risk of developing various health problems, both mental and physical. Victims often experience mental health challenges such as depression, anxiety, and sleep disorders, as well as physical symptoms such as headaches, muscle tension, insecurity in the school environment, and decreased interest and academic performance. Incidents of bullying among students are increasing at all levels of education, highlighting the urgent need for effective prevention and intervention strategies. These efforts include utilizing the Indonesian language as a tool to convey the causes and harmful effects of bullying behavior. The goal of this initiative is to raise awareness about basic knowledge of bullying by emphasizing the role of language as a form of social control. By increasing students' understanding and awareness, it is hoped that they will be better able to avoid becoming involved in or becoming victims of bullying in the school environment. Sustained socialization efforts are expected to support students in using language responsibly as a means of maintaining social harmony.ABSTRAKPerundungan melibatkan penyalahgunaan kekuasaan untuk menyakiti individu atau kelompok melalui cara verbal, fisik, atau psikologis, yang membuat korban merasa tertekan, trauma, dan tidak berdaya. Remaja yang mengalami perundungan berisiko lebih tinggi mengalami berbagai masalah kesehatan, baik mental maupun fisik. Korban sering mengalami tantangan kesehatan mental seperti depresi, kecemasan, dan gangguan tidur, serta gejala fisik seperti sakit kepala, ketegangan otot, ketidakamanan di lingkungan sekolah, dan penurunan minat dan prestasi akademik. Insiden perundungan di kalangan siswa meningkat di semua tingkatan pendidikan, menyoroti kebutuhan mendesak akan strategi pencegahan dan intervensi yang efektif. Upaya ini termasuk memanfaatkan bahasa Indonesia sebagai alat untuk menyampaikan penyebab dan dampak merugikan perilaku perundungan. Tujuan inisiatif ini adalah untuk meningkatkan kesadaran tentang pengetahuan dasar mengenai perundungan dengan menekankan peran bahasa sebagai bentuk kontrol sosial. Dengan meningkatkan pemahaman dan kesadaran siswa, diharapkan mereka akan lebih mampu menghindari terlibat dalam atau menjadi korban perundungan di lingkungan sekolah. Upaya sosialisasi yang berkelanjutan diharapkan dapat mendukung siswa dalam menggunakan bahasa secara bertanggung jawab sebagai sarana untuk menjaga harmoni sosial.